Biomechanical analysis of motion following sacroiliac joint fusion using lateral sacroiliac screws with or without lumbosacral instrumented fusion. (August 2019) - Dall, Bruce E.; Eden, Sonia V.; Cho, Woojin; Karkenny, Alexa; Brooks, Daina M.; Hayward, Gerald M.; Moldavsky, Mark; Yandamuri, Soumya; Bucklen, Brandon S.
Abstract: Background: Sacroiliac joint hypermobility or aberrant mechanics may be a source of pain. The purpose of this study was to assess sacroiliac joint range of motion after simulated adjacent lumbosacral instrumented fusion, with or without sacroiliac joint fusion, with lateral sacroiliac screws. Methods: In this in vitro biomechanical study, seven cadaveric specimens were tested on a six-degrees-of-freedom machine under load control. Left posterior sacroiliac joint ligaments were severed to maximize joint range of motion. Influence of lumbosacral instrumentation on sacroiliac joint motion, with or without fixation, was studied. Findings: During flexion-extension in the setting of posterior sacroiliac joint injury and L5–S1 fixation, sacroiliac joint range of motion increased to 195% of intact. After fixation with lateral sacroiliac screws, average range of motion reduced to 144% of intact motion. Sacroiliac joint screws thus partially stabilized the joint and reduced motion. Use of 6 bilateral sacroiliac joint screws with L5–S1 screw and rod fixation in lateral bending and axial rotation yielded the greatest reduction in range of motion. Without lumbosacral fixation, baseline motion of the sacroiliac joint was reduced, and sacroiliac joint screw alone, using either 2, 3, or 6 screws, was able to restore motion at or below the level of an intact joint. Interpretation: Sacroiliac joint ligament injury with existing lumbosacral fixation doubled sacroiliac joint range of motion, but thereafter, fixation with lateral sacroiliac screws decreased range of motion of the injured sacroiliac joint. Screw configuration played a minor role, but generally, 6 sacroiliac joint screws had the greatest motion reduction. Highlights: The greatest sacroiliac junction range of motion was seen during flexion-extension. The sacroiliac joint is an inherently stable joint with minimal range of motion. Posterior ligament injury may be attributed to sacroiliac joint instability. Previous lumbosacral posterior fixation increases motion between the joint.